2000
DOI: 10.1046/j.1365-2044.2000.01547-4.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of anaesthetists to identify a marked lumbar interspace

Abstract: SummaryA computerised database of operating theatre activity was used to estimate the costs of regional and general anaesthesia for varicose vein and inguinal hernia surgery. Data retrieved for each procedure included the anaesthetic technique and drugs used, and the duration of anaesthesia, surgery and recovery. The costs of anaesthetic drugs and disposables, salary costs of the anaesthetic personnel and maintenance costs for anaesthetic equipment were considered. Drugs and disposables accounted for < 25% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
243
3
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 381 publications
(277 citation statements)
references
References 8 publications
10
243
3
13
Order By: Relevance
“…A high frequency (7)(8)(9)(10)(11)(12)(13)(14)(15) MHz) linear transducer is preferred for peripheral nerve blocks and central venous cannulations where the structures to be visualized are located superficially. This transducer produces a high-resolution image; however, it has poor beam penetration.…”
Section: Basic Concepts Of Spinal Ultrasoundmentioning
confidence: 99%
See 4 more Smart Citations
“…A high frequency (7)(8)(9)(10)(11)(12)(13)(14)(15) MHz) linear transducer is preferred for peripheral nerve blocks and central venous cannulations where the structures to be visualized are located superficially. This transducer produces a high-resolution image; however, it has poor beam penetration.…”
Section: Basic Concepts Of Spinal Ultrasoundmentioning
confidence: 99%
“…11 Broadbent et al demonstrated that even experienced anesthesiologists estimate the intervertebral level inaccurately by palpation in 71% of cases; they tend to estimate the level as higher than the actual, and their estimate could be as many as four spaces higher. 12 Tuffier's line, an anatomical landmark widely used for this purpose, does not always bear a constant relationship to an individual vertebral level or the interspace. Particularly in pregnant women, Tuffier's line intersects the spine above L4-5 interspace level, and the median level of intersection is just below L2-3 level.…”
Section: Efficacy Of Ultrasound-guided Techniquesmentioning
confidence: 99%
See 3 more Smart Citations